Investigating the Effects of Test Accommodations with Process Data for English Learners in a Mathematics Assessment. Issue 1 (2nd January 2022) - Wolf, Mikyung Kim; Yoo, Hanwook; Guzman-Orth, Danielle; Abedi, Jamal
ABSTRACT: Implementing a randomized controlled trial design, the present study investigated the effects of two types of accommodations, linguistic modification and a glossary, for English learners (ELs) taking a computer-based mathematics assessment. Process data including response time and clicks on glossary words were also examined to better interpret students' interaction with the accommodations in the testing conditions. Regression and ANOVA analyses were performed with data from 513 students (189 ELs and 324 non-ELs) in Grade 9. No statistically significant accommodation effects were detected in this study. Process data revealed possible explanations (i.e., student engagement and glossary usage) for the nonsignificant results. Implications for future research on test accommodations for EL students are discussed.